The Czech Vienna school and the art of the “small people" - Marta Filipová (Journal of Art Historiography, 2020)
The article focuses on the attitudes of the Vienna school followers to folk art and primarily examines the writing of the Czech art historians, Zdeněk Wirth and Antonín Matějček. Their attention to art created by the small people of villages and the countryside had clear parallels in the theories of Alois Riegl. Both Czech art historians, however, developed Riegl's views further. Aware of the impact of modernity and industrialisation on art production, they related folk art to a specific class and the social, economic and ethnic changes in the Czech lands in the first two decades of the twentieth century. The text therefore scrutinises their reasons for the continued concern with folk art in the light of the legacy of the Vienna school.